2009
DOI: 10.1103/physrevb.79.205320
|View full text |Cite
|
Sign up to set email alerts
|

Phase study of oscillatory resistances in microwave-irradiated- and dark-GaAs/AlGaAs devices: Indications of an unfamiliar class of the integral quantum Hall effect

Abstract: We report the experimental results from a dark study and a photo-excited study of the high mobility GaAs/AlGaAs system at large filling factors, ν. At large-ν, the dark study indicates several distinct phase relations ("Type-1", "Type-2", and "Type-3") between the oscillatory diagonal-and Hall-resistances, as the canonical Integral Quantum Hall Effect (IQHE) is manifested in the "Type-1" case of approximately orthogonal diagonal-and Hall resistance-oscillations. Surprisingly, the investigation indicates quantu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 65 publications
0
36
0
Order By: Relevance
“…In general, for a system showing Landau level quantization, the increased degeneracy of Landau levels leads to enhanced density of state near the Fermi level under high magnetic fields, which effectively amplifies the electron correlation effect [90][91][92]. This effect is expected to be particularly strong for the α-Dirac band of ZrSiS since the quantum limit of this band can be easily reached due to its low oscillation frequency (F α ~8.4T).…”
Section: Discussionmentioning
confidence: 99%
“…In general, for a system showing Landau level quantization, the increased degeneracy of Landau levels leads to enhanced density of state near the Fermi level under high magnetic fields, which effectively amplifies the electron correlation effect [90][91][92]. This effect is expected to be particularly strong for the α-Dirac band of ZrSiS since the quantum limit of this band can be easily reached due to its low oscillation frequency (F α ~8.4T).…”
Section: Discussionmentioning
confidence: 99%
“…Tung et al examined long Hall bars and Corbino rings at sub-millimeter wave frequencies, and reported a double lock-in photo-resistance signal up to 495 GHz. 23 Other experimental work by Mani et al 1,17,21,22 also indicated zero-resistance states and radiation-induced magneto-resistance oscillations in R xx above 100GHz.…”
mentioning
confidence: 87%
“…Note that at these relatively large f , these radiation-induced oscillations do overlap the morerapidly-varying-with-B Shubnikov-de Haas (SdH) oscillations, see also ref. 17,21,22 . A close comparison of Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The huge photo-induced modulation of the dark magnetoresistance in this special photo-response of the 2DES yields potential applications in microwave and terahertz wave sensing. 3 The amplitude of the radiation-induced magnetoresistance oscillations (RiMOs) depends on factors such as radiation frequency [4][5][6] ; temperature 7 , radiation power 8 , linear polarization direction 9,10 , angle between magnetic field and sample normal 11 and current through sample 12 . All these factors have been examined both experimentally [13][14][15][16][17][18][19][20][21][22][23] and theoretically .…”
Section: Introductionmentioning
confidence: 99%